1991
DOI: 10.1111/j.1439-0531.1991.tb01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep Freezing of Boar Semen Packaged in Plastic Bags and Straws

Abstract: Contents: For practical reasons, a large volume (i.e. 5 ml) of frozen boar semen per insemination dose is desirable, but successful freezing has not been achieved, since optimal cooling rates have not yet been established. Post‐thaw motility and the acrosome intep'ty of semen from four boars frozen with a programmable freezin machine, in mini‐(0.25 ml), maxi‐(5 ml) plastic straws and in 10 × 5 cm PVC‐ or Teflon FEP‐plastic bags (0.35–0.12 mm thick, 5 ml) was studied. The freezing of the semen was monitored us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 10 publications
2
29
1
1
Order By: Relevance
“…Postthaw motility and duration of sperm motility of Matrinxã (Brycon orthotaenia) was higher when frozen in DMSO than either propylene glycol or ethylene glycol (Melo & Godinho 2006). The use of one-step freezing rate at between 5 or 8°C min À1 was sufficient for cryopreservation of B. gonionotus sperm, indicating that there was no need to use stepwise freezing rate, which is commonly used in mammalian sperm cryoprerservation (Bwanga, Einarsson & Rodriguez-Martinez 1991). Low freezing rate also yielded good postthaw sperm motility in other fish species including striped catfish (Pangasius hypophthalmus; Kwantong & Bart 2003), common carp (Cyprinus carpio; Irawan et al 2010) and olive barb (P. sarana; Nahiduzzaman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Postthaw motility and duration of sperm motility of Matrinxã (Brycon orthotaenia) was higher when frozen in DMSO than either propylene glycol or ethylene glycol (Melo & Godinho 2006). The use of one-step freezing rate at between 5 or 8°C min À1 was sufficient for cryopreservation of B. gonionotus sperm, indicating that there was no need to use stepwise freezing rate, which is commonly used in mammalian sperm cryoprerservation (Bwanga, Einarsson & Rodriguez-Martinez 1991). Low freezing rate also yielded good postthaw sperm motility in other fish species including striped catfish (Pangasius hypophthalmus; Kwantong & Bart 2003), common carp (Cyprinus carpio; Irawan et al 2010) and olive barb (P. sarana; Nahiduzzaman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal temperature and duration of thawing for cryopreserved boar sperm might logically depend on the packaging material, form, and volume [1,[11][12][13][14] to optimize the surface area-to-volume ratio to allow for uniform thawing [11,15,16]. Cryopreserved boar sperm is routinely thawed in the range of 37 C to 70 C for 5 to 40 seconds [16,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreserved boar sperm is packaged in plastic straws or plastic bags of 0.25 to 5 mL volumes [1,[11][12][13][14]. In some research studies, improved postthaw quality was observed in lower-volume straws and plastic bags (0.25-0.7 mL) because of the smaller surface area-tovolume ratio, which allows for more uniform freezing and thawing [11,15,16]. Because of the discrepancies in freezing volume, surface area, and surface area-to-volume ratio, different thawing temperatures and durations have been explored for sperm packaged in different forms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the semen collection technique, equilibration time, type of semen extender, type and concentration of cryoprotectant, freezing package, freezing rate and thawing procedure (Johnson et al, 2000). Many types of freezing package have been used for frozen boar semen, such as medium straws, maxi straws (Bwanga et al, 1991;Berger and Fisherleitner, 1992), plastic bags (Bwanga et al, 1991) and FlatPack ® /MiniFlatPack ® (Eriksson and Rodriguez-Martinez, 2000). Most containers has been developed for suitable storage, transport, post thawed semen quality and practical insemination.…”
Section: Cryopreservation Of Animal Spermatozoamentioning
confidence: 99%
“…However, a great variation on the survival rate of post-thawed spermatozoa are obtained, due to the lack of biological background concerning the cryopreservation technique (Buranaamnuay et al, 2006 a,b ). During the recent years, studies on FT boar semen have dramatically improved boar semen cryopreservation technique, for instance, optimum freezing protocols (Eriksson and Rodrigrez-Martinez, 2000), types of freezing package (Bwanga et al, 1991;Berger and Fisherleitner, 1992;Bwanga et al, 1991;Eriksson and Rodriguez-Martinez, 2000), semen centrifugation methods (Carvajal et al, 2004), thawing process (Eriksson and Rodrigrez-Martinez, 2000;Córdova-Izquierdo et al, 2006) and the supplement of some additives to the semen extender (Peña et al, 2003, Gadea et al, 2004Roca et al, 2004Roca et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%